Beef, Chicken, and Soy Proteins in Diets Induce Different Gut Microbiota and Metabolites in Rats - Zhu, Yingying; Shi, Xuebin; Lin, Xisha; Ye, Keping; Xu, Xinglian; Li, Chunbao; Zhou, Guanghong (Frontiers in Microbiology, 2017)
Previous studies have paid much attention to the associations between high intake of meat and host health. Our previous study showed that the intake of meat proteins can maintain a more balanced composition of gut bacteria as compared to soy protein diet. However, the associations between dietary protein source, gut bacteria and host health were still unclear. In this study, we collected colonic contents from the growing rats fed with casein, beef, chicken or soy proteins for 90 days, and analyzed the compositions of gut microbiota and metabolites. Compared to the casein group (control), the chicken protein group showed the highest relative abundance of Lactobacillus and the highest levels of organic acids, including lactate, which can in turn promote the growth of Lactobacillus. The soy protein group had the highest relative abundance of Ruminococcus but the lowest relative abundance of Lactobacillus. Long-term intake of soy protein led to the up-regulation of transcription factor CD14 receptor and lipopolysaccharide-binding protein in liver and serum, an indicator for elevated bacterial endotoxins. In addition, the intake of soy protein also increased the levels of glutathione S-transferases in liver, which implicates elevated defense and stress responses. These results confirmed that meat protein intake may maintain a more balanced composition of gut bacteria and reduce the antigen load and inflammatory response from gut bacteria to the host.